2020
DOI: 10.1111/jcpp.13176
|View full text |Cite
|
Sign up to set email alerts
|

Annual Research Review: Looking back to look forward – changes in the concept of autism and implications for future research

Abstract: The concept of autism is a significant contribution from child psychiatry that has entered wider culture and public consciousness, and has evolved significantly over the last four decades. Taking a rather personal retrospective, reflecting on our own time in autism research, this review explores changes in the concept of autism and the implications of these for future research. We focus on seven major changes in how autism is thought of, operationalised, and recognised: (1) from a narrow definition to wide dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
179
1
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(198 citation statements)
references
References 97 publications
(102 reference statements)
3
179
1
15
Order By: Relevance
“…Prior work has suggested that the core dyad of SC and RRB is fractionable at behavior and neural levels and is underpinned by different genetic mechanisms [4][5][6][7][8][9][10][11][12][13][14] . However, it is unclear whether the road from genome to phenome (e.g., Figure 1) is one that converges on a common pathway or is one of multiple pathways 15 . Here we find evidence more in line with the multiple pathways model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work has suggested that the core dyad of SC and RRB is fractionable at behavior and neural levels and is underpinned by different genetic mechanisms [4][5][6][7][8][9][10][11][12][13][14] . However, it is unclear whether the road from genome to phenome (e.g., Figure 1) is one that converges on a common pathway or is one of multiple pathways 15 . Here we find evidence more in line with the multiple pathways model.…”
Section: Discussionmentioning
confidence: 99%
“…These subtypes might be underpinned by a common pathway if they showed similar neural circuit and genomic mechanisms that differ from a typically-developing (TD) comparison group. However, based on the idea that SC and RRB domains are fractionable across multiple levels, it could be that these subtypes diverge onto multiple pathways from genome to phenome 15 (Figure 1). This idea has not yet been tested with respect to macroscale neural circuitry and its link to functional genomic mechanisms.…”
mentioning
confidence: 99%
“…The pre-determined inclusion criteria were [1] only published, peer-reviewed English language journals; [2] studies of any design (quantitative or qualitative) focusing on CR interventions and ASC [3] empirical studies that include either adolescents or adults [4] studies using any modality of treatment e.g. individual sessions or group sessions.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…In the 1980s, ASC was considered uncommon with a prevalence estimate of around 22 in 10,000 (3). Nonetheless, with increasing recognition the ASC prevalence estimate is now considered to be approximately one in 100 and relatively common (4).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the research project could become a mutually beneficial endeavour to both me as researcher and the autistic participants who were lending me their time. Co-production with autistic stakeholders, and autistic scholarship that brings autistic voices into the academy, are, rightly, increasingly being recognized as providing vital insights for autism research (Chown et al, 2017;Happé and Frith, 2020;Milton and Bracher, 2013;Pellicano, 2020). However, it remains the case that 'the vast majority of research in autism is still undertaken on autistic people, rather than with them, and is often not concerned with improving the day-to-day lives of people with autism' (Milton and Bracher, 2013: 2).…”
Section: Introductionmentioning
confidence: 99%